PENGARUH BEBAN GAS TERHADAP PENYERAPAN GAS CO2 DALAM ABSORPSI CAMPURAN UDARA DAN GAS CO2 OLEH LARUTAN K2CO3 PADA PACKED COLUMN - Kusnarjo Kusnarjo (Purifikasi, 2008)
This research was aimed to study the influence of gas loading on CO2 absorbance quantity in CO2 and air flow. Potassium carbonate solution was contacted counter currently in a 10 cm diameter and 150 cm high raschig ring packed column. The packing was prepared from 1.0 cm diameter and 2 cm high aluminium alloy, which was filled in a column of 100 cm high. CO2 was applied from the bottom and K2CO3 solution was added counter currently from the top of the column. The inlet gas consisted of pure CO2 and mixture of CO2 and air containing 20% mole CO2. The gas flow rate varied from 8 to 24 L/minute, and the liquid flow rate was varied from 3 to 7 L/minute. The concentration of K2CO3 in liquid inlet varied from 1 M and 1,5 M. The research result showed that in pure CO2 and 1M K2CO3 concentration, the CO2 absorption efficiency increased from 3.79 to 13.54 % and in 1.5 M K2CO3 concentration, the CO2 absorption efficiency increased from 3.90 to 13.80 %. In CO2 concentration of 20% with K2CO3 solution of 1 M concentration the, CO2 absorption efficiency increased from 7.88 to 16.37 %. The CO2 absorption increased from 11.22 to 16.87% in K2CO3 concentration of 1.5 M.